2008
DOI: 10.1002/jsfa.3206
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid content and antioxidant capacity of spinach genotypes determined by high‐performance liquid chromatography/mass spectrometry

Abstract: BACKGROUND: Flavonoids in different spinach genotypes were separated, identified, and quantified by a high-performance liquid chromatographic method with photodiode array and mass spectrometric detection. The antioxidant capacities of the genotypes were also measured using two antioxidant assays-oxygen radical absorbance capacity (ORAC FL ) and photochemiluminescence (PCL)-which measure the response to the peroxyl and superoxide anion radicals, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
45
2
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 36 publications
9
45
2
4
Order By: Relevance
“…The HPLC profiles of these samples were very much the same (data not shown). Based on our MS/MS data and the spinach flavonoids MS data provided in literature (Bergquist, Gertsson, Knuthsen, & Olsson, 2005;Cho, Howard, Prior, & Morelock, 2008), the major flavonoids in the spinach samples were tentatively identified as: peak 1, patuletin-3-glucosyl-(1 ? 6)[apiosyl(1 ?…”
Section: Effect Of Ane Treatment On Flavonoid Content Of Spinach Leavesmentioning
confidence: 89%
See 1 more Smart Citation
“…The HPLC profiles of these samples were very much the same (data not shown). Based on our MS/MS data and the spinach flavonoids MS data provided in literature (Bergquist, Gertsson, Knuthsen, & Olsson, 2005;Cho, Howard, Prior, & Morelock, 2008), the major flavonoids in the spinach samples were tentatively identified as: peak 1, patuletin-3-glucosyl-(1 ? 6)[apiosyl(1 ?…”
Section: Effect Of Ane Treatment On Flavonoid Content Of Spinach Leavesmentioning
confidence: 89%
“…Spinach extracts have been studied in both in vitro and in vivo systems, and are widely shown to possess anti-inflammatory effects, anti-mutagenic potential, anti-neoplastic effects, as well as chemo-preventive activities (Boivin et al, 2009;Hait-Darshan, Grossman, Bergman, Deutsch, & Zurgil, 2009). These activities in spinach were found to be superior to those of the well-documented antioxidants such as EGCG, ascorbic acid, and vitamin E, probably due to the broad free radical scavenging capacity of the natural antioxidants, especially the novel antioxidant glucuronated flavonoids (Bergman, Perelman, Dubinsky, & Grossman, 2003;Cho et al, 2008) in spinach. Here for the first time, we demonstrated that spinach extracts are capable of modulating the normal lifespan of wild type C. elegans Bristol N2.…”
Section: Ane-treated Spinach Imparts Increased Resistance To Stressesmentioning
confidence: 97%
“…The roots of celery, and Jerusalem artichoke, the aerial parts of spinach, chard, purslane, ispit, and garden rocket, the leaves of red cabbage, lime flower, the fruit of rosehip and the bark of cinnamon were used to prepare the extracts. In fact, there are some antioxidant activity studies on these eleven plant extracts (Yildirim et al, 2000;Pyo et al, 2004;Su et al, 2007;Cho et al, 2008;Sacan et al, 2008;Huang et al, 2009;Jagdish et al, 2009). In this study, the antioxidant activity of the selected plants was carried out for the first time using the cupric reducing antioxidant capacity (CUPRAC) method which was introduced and developed by Apak et al (2004).…”
Section: Introductionmentioning
confidence: 96%
“…In addition to the major food constituents such as protein, fat, carbohydrate and micronutrients such as vitamins, minerals and trace elements, fruit and vegetables contain other compounds that may have a positive effect on human health. These phytochemicals include groups of compounds such as carotenoids, flavonoids, polyphenols and other phenolic acids and glucosinolates (Kris-Etherton, Harris, & Appel, 2002;Cho, Howard, Prior, & Morelock, 2008). These phytochemicals are collectively called as bioactive compounds and are thought to be potential antioxidants.…”
Section: Introductionmentioning
confidence: 99%